Problematika kardiovaskulárni toxicity koxibů a neselektivních NSA - Forejtová, S (Vnitrni lekarstvi, 2006)
Non-steroidal antirheumatics (NSA) belong to the most often prescribed drugs. Certain observation studies indicate that they are used by 20 to 30% of population of developed countries. The most common NSA's adverse effects are gastrointestinal complications. Coxibs have been developed as an alternative to conventional non-selective NSA; with similar efficacy, they should reduce the risk of development of gastrointestinal complications. In the few last years, possible toxicity of coxibs and other non-steroidal antirheumatics has been widely discussed. The VIGOR study, which was performed 6 years ago, showed five times higher incidence of nonfatal myocardial infarction in patients with rofecoxib therapy as compared with naproxen. Afterwards, there was much debate about rofecoxib, and coxibs in general, whose cardiotoxicity was supported and confuted at the same time. Possible cardioprotective effect of naproxen was discussed too. Later on, results of the APPROVE study (Adenoma Polyp Prevention on Vioxx) made Merck & Co., Inc. withdraw rofecoxib from all markets voluntarily. In the end of 2004, three controversial studies on celecoxib were published. Although the first study (Adenoma Prevention with Celecoxib study, APC) showed higher cardiovascular risk of celecoxib, the second study (Prevention of Adenomatosus Polyps, PreSAP) did not verify these results. Surprisingly, the third study (Alzheimer Disease and Prevention Trial, ADAPT) proved 50% increase of the risk of cardiovascular (CV) toxicity of naproxen. In the last year, researchers have tried to decide whether CV toxicity is a class effect of coxib group or a class effect of all NSA. Many observation studies proved higher CV risk both of coxibs (particularly rofecoxib) and non-selective NSA including naproxen. These new findings moved the American FDA (Food and Drug Administration) to publish guidance concerning higher CV risk of all coxibs and NSA. For the time being, the EMEA (European Agency for Evaluation of Medicinal Products) does not change its attitude to NSA; coxibs are contraindicated in patients with ischemic heart disease, cerebrovascular disease and peripheral artery disease; they should be used with caution in high-risk patients. Final assessment of the problems of CV toxicity of NSA and coxibs will be a case of a long-term randomized study focused on the incidence of cardiovascular adverse effects.
Keywords: Cyclooxygenase Inhibitors; kardiovaskulární nemoci; Anti-Inflammatory Agents, Non-Steroidal; Humans; Cardiovascular Diseases; inhibitory cyklooxygenasy; lidé; antiflogistika nesteroidní